2020
DOI: 10.1101/2020.04.01.019430
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Adhatoda Vasica rescues the hypoxia dependent severe asthma symptoms and mitochondrial dysfunction

Abstract: Severe asthma is chronic airway disease, exhibit poor response to conventional asthma therapies.Growing evidence suggests that elevated hypoxia increases the severity of asthmatic inflammation among patient and model systems. In this study, we elucidate the therapeutic effect and mechanistic basis of Adhatoda Vasica (AV) aqueous extract on acute allergic as well as severe asthma subtypes, at physiological, histopathological and molecular levels using mouse models.We observed, oral administration of AV extract … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…However, none of the studies have so far studied the effect of AV on molecular markers of asthma/in ammation phenotype in its aqueous extract form prescribed in Ayurveda. For the rst time, we have shown that the anti-asthmatic effect of AV is not only limited to acute asthmatic features but it also alleviates the severe airway in ammation in steroid-nonresponsive asthmatic mice [14]. We show that the AV extract causes inhibition of HIF-1α (key transcription factor in hypoxia) by increasing the expression of its negative regulator, PHD2, thereby modulates hypoxic response, which forms the basis for its diverse therapeutic effects [14].…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…However, none of the studies have so far studied the effect of AV on molecular markers of asthma/in ammation phenotype in its aqueous extract form prescribed in Ayurveda. For the rst time, we have shown that the anti-asthmatic effect of AV is not only limited to acute asthmatic features but it also alleviates the severe airway in ammation in steroid-nonresponsive asthmatic mice [14]. We show that the AV extract causes inhibition of HIF-1α (key transcription factor in hypoxia) by increasing the expression of its negative regulator, PHD2, thereby modulates hypoxic response, which forms the basis for its diverse therapeutic effects [14].…”
Section: Discussionmentioning
confidence: 94%
“…For the rst time, we have shown that the anti-asthmatic effect of AV is not only limited to acute asthmatic features but it also alleviates the severe airway in ammation in steroid-nonresponsive asthmatic mice [14]. We show that the AV extract causes inhibition of HIF-1α (key transcription factor in hypoxia) by increasing the expression of its negative regulator, PHD2, thereby modulates hypoxic response, which forms the basis for its diverse therapeutic effects [14]. Further, AV treatment to lung epithelial cells has also been shown to reduce hypoxia's downstream impact such as mitochondrial dysfunction [14].…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations